2019
DOI: 10.1038/s41598-019-48867-x
|View full text |Cite
|
Sign up to set email alerts
|

Construction of complete Tupaia belangeri transcriptome database by whole-genome and comprehensive RNA sequencing

Abstract: The northern tree shrew ( Tupaia belangeri ) possesses high potential as an animal model of human diseases and biology, given its genetic similarity to primates. Although genetic information on the tree shrew has already been published, some of the entire coding sequences (CDSs) of tree shrew genes remained incomplete, and the reliability of these CDSs remained difficult to determine. To improve the determination of tree shrew CDSs, we performed sequencing of the whole-genome, mRNA, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 37 publications
0
14
0
1
Order By: Relevance
“…Tree shrews (Tupaia belangeri chinensis), belongs to the family Tupaiidae, genus Tupaia, are rat-sized mammal that live mainly in deciduous, evergreen and secondary forests in tropical and subtropical regions (1). Whole-genome sequencing analysis has revealed that tree shrews are similar to humans with regard to histology, physiology, biochemistry, and nervous (brain function), metabolic and immune systems (2)(3)(4). The tree shrew is small, has a short reproductive cycle, is easy to perform experiments on, is inexpensive to feed, and has other favorable characteristics, such as susceptible to a wide range of human pathogenic viruses (5).…”
Section: Introductionmentioning
confidence: 99%
“…Tree shrews (Tupaia belangeri chinensis), belongs to the family Tupaiidae, genus Tupaia, are rat-sized mammal that live mainly in deciduous, evergreen and secondary forests in tropical and subtropical regions (1). Whole-genome sequencing analysis has revealed that tree shrews are similar to humans with regard to histology, physiology, biochemistry, and nervous (brain function), metabolic and immune systems (2)(3)(4). The tree shrew is small, has a short reproductive cycle, is easy to perform experiments on, is inexpensive to feed, and has other favorable characteristics, such as susceptible to a wide range of human pathogenic viruses (5).…”
Section: Introductionmentioning
confidence: 99%
“…The antiviral gene RIG-I (retinoic acid inducible gene I) was also lost during evolution (14). As a close relative of non-human primates, the whole genome of the tree shrew has been sequenced, and the results show that the nervous, immune and metabolic systems of the tree shrew are similar to those of humans (15)(16)(17). The relevant genomic data can be queried in the tree shrew database (TreeshrewDB) (http:// www.treeshrewdb.org) (18).…”
Section: Introductionmentioning
confidence: 99%
“…Tupaia belangeri is a small non-primate mammal belonging to the family Tupaiidae, which has a body weight of approximately 150 g [4]. In comparison with rodents, the genome sequence of tree shrew shows a higher homology with that of primates [4][5][6]. The tree shrew shows susceptibility to hepatitis viruses infections (hepatitis C virus [7,8], hepatitis B virus [9,10]) and can be used for the evaluation of anti-depressant drugs [11].…”
Section: Introductionmentioning
confidence: 99%